A managerial perspective of dynamic capabilities in emerging markets: The case of the Russian steel industry - Gregory Ludwig; Jon Pemberton (Journal for East European Management Studies, 2011)
The paper critiques current thinking in the area of dynamic capabilities, exploring and challenging previous research on Dynamic Capabilities (DC) utilizing an application and empirical research within the Russian steel industry. Multiple sources of evidence arising from an in-depth study over a period of three years are deployed including semi-structured interviews with senior managers, as well as internal management reports, and other documentary evidence. The research concludes that practitioners need not choose between either routine-building on the one hand, or radical renewal on the other, but must recognize that dynamisms typically derive from the establishment of respective internal processes, followed by rapid-decision making. – – Der vorliegende Beitrag befasst sich kritisch mit dem momentanen Wissensstand auf dem Spezialgebiet der 'Dynamic Capabilities' (DC). Dies geschieht durch eine praktische Anwendung von Strategietheorie, kombiniert mit einer intensiven Datenerhebung in der Stahlindustrie der Russischen Föderation. Über einen Zeitraum von drei Jahren wurden empirische Daten durch zahlreiche aufgezeichnete Gespräche mit Topmanagern gesammelt, desweiteren interne und vertrauliche Berichte und andere industriespezifische Dokumente anlaysiert. Der fundierte Fachartikel schlussfolgert dass die Entwicklung von Dynamic Capabilities, ein Prozess der von Topmanagern geleitet und durchgeführt werden sollte, hauptsächlich interner und firmenspezifischer Natur ist und vor allem auf gezielten Entscheidungs-und Denkprozessen beruht.
Keywords: 650; strategy; dynamic capabilities; the Russian Federation; steel industry